Exploring Emerging Antifungal Drugs Regime for Aspergillus-Associated Infections - Thakur, Raman; Такур, Раман (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Aspergillus species, a group of fungi, can cause various infections, especially in individuals with a weakened immune system. The increasing prevalence of Aspergillus-associated or other fungal infections highlights the urgent need for improved antifungal therapies and preventive strategies, especially as fungal resistance becomes an emerging concern within healthcare settings. New antifungal agents such as ibrexafungerp, olorofim, fosmanogepix, and rezafungin are transforming the treatment of fungal infections by addressing issues of drug resistance, toxicity, and limited efficacy against certain strains. Current antifungal treatments face significant limitations, including the emergence of drug resistance among fungal pathogens, which complicates the treatment of previously manageable infections. Emerging antifungal drugs, such as voriconazole, posaconazole, ravuconazole, SPE-843, and T-2307, are crucial in addressing the growing concern of antifungal resistance and providing alternative treatment.  The integration of these innovative antifungal drugs into clinical practice is expected to significantly improve patient management and outcomes in fungal infections. Immunotherapy plays a crucial role in enhancing the immune response against Aspergillus spp. infections, particularly when combined with antifungal agents. The integration of immunotherapy with antifungal treatments, known as combination therapy, is gaining traction as it can help overcome resistance and enhance therapeutic efficacy. Immune modulation during Aspergillus infection is crucial for enhancing host immune responses and developing potential combination therapies. Synergistic mechanisms include blocking PD-1, using cytokines such as IFN-γ and G-CSF, and exploring strategies like NK cell transfer and CAR T-cell therapy to boost immune responses against Aspergillus. Antifungal agents can also modulate the activity of phagocytes, enhancing their antifungal responses through specific receptor interactions. However, challenges remain in translating these findings into clinical practice, necessitating well-designed clinical trials to establish the safety and efficacy of these combined approaches in diverse patient populations.